Analysis of the Implementation of the Integrated Ethnoscience Project-Based Learning (PjBL) Model in NTT Ikat Weaving Dyeing for High School Chemistry Learning - Visensia H. B. Hayon; Theresia Wariani; Yanti Rosinda Tinenti; Alfons Bunga Naen; Hironimus Tangi; Florentina Yasinta Sepe; Ana Maria Derosari (Postgraduate, University of Mataram, 2026)
This study aims to comprehensively analyze the implementation of the Project-Based Learning (PjBL) Model integrated with ethnoscience in NTT Ikat Weaving dyeing in Chemistry learning at high schools, including its impact, critical challenges, and strategies for strengthening the competencies of teachers and students. This study uses a qualitative method with a descriptive analytical approach. The research subjects consisted of Chemistry teachers as model implementers and 11th-grade students involved in the learning project. The main research instruments used included observation sheets on the implementation of PjBL focusing on teacher performance, teacher questionnaires, student questionnaires, in-depth interviews with teachers, and in-depth interviews with students. The results show that the implementation of this model was very good (above 82%) in terms of PjBL syntax and ethnoscience integration, providing a significant positive impact in the form of increased motivation, student involvement, and teacher self-efficacy, as well as an increase in the understanding of contextual chemistry concepts. However, the implementation faced critical challenges, particularly in terms of logistical constraints and rigid curriculum time allocation, as well as weaknesses in teacher assessment instruments and criteria (Column 3 criteria were rated the lowest, x̄ = 3.27). For sustainability, a strategy to strengthen teacher competencies is needed through research collaboration with local artisans and institutional support in providing logistics and adjusting curriculum time allocation. Overall, integrated PjBL ethnoscience has proven to be effective and transformative, but its optimization is highly dependent on strong systemic support.